Utilization of Palm Waste Charcoal Briquettes (ABLS) as Thematic-based Integrated Science Learning Materials for Middle School Students - Sausan Fatin Nurazizah; Rendy Wikrama Wardana; Bhakti Karyadi; Henny Johan; Deni Parlindungan; Fitri Mulyani; Lasriani Lasriani (Pascasarjana Universitas Negeri Malang (UM), 2023)
This investigation was conducted with the objective of evaluating the efficacy of ABLS ignition and formulating instructional materials for junior high school science education through the integration of e-booklets containing thematic-based science content. The research design employed herein adheres to the principles of experimentation and model development, falling under the category of Research and Development (R&D). The experimental cohort was stratified into three groups denoted as A1 (70% shell charcoal: 30% bunch charcoal), A2 (50% shell charcoal: 50% bunch charcoal), and A3 (30% shell charcoal: 70% bunch charcoal). The development of science learning materials was realized through integration with cobwebs, and subsequently, these materials were formatted into e-booklets. The outcomes of the ABLS ignition quality assessment revealed that composition A1 exhibited the optimal ignition proficiency, requiring 14 minutes to achieve the boiling of 100 ml of water, followed by composition A2 (16 minutes) and A3 (18 minutes). Subsequent ABLS testing, specifically ash analysis, yielded values of 6 grams for A1, 7 grams for A2, and 8 grams for A3. The flame coloration in compositions A1 and A2 manifested as bluish-red, devoid of smoke, whereas A3 displayed a red flame with minimal smoke emission. In conclusion, the ABLS ignition quality test substantiates that a charcoal composition ratio of 70% shell charcoal to 30% bunch charcoal yields the most favorable results. The thematic framework for junior high school science education, centered around the ABLS theme, encompasses six key topics: Classification of Material and Its Changes, Temperature and Changes, Energy and Living Systems, Environmental Pollution, Substance Pressure and Its Application in Daily, and Environmentally Friendly Technology. This study affirms that the ABLS theme holds potential for development into a cohesive thematic model for natural science teaching materials in junior high schools.DOI: 10.17977/jps.v11i22023p035